Development of the Image of the Coastal Area of Surabaya as Improving Regional Economic Potential and Support Surabaya City Government Development Program - Tri Aphief Artanto; Aryo Bayu Wibisono (Future Science)
Coastal areas have the potential to thrive in today's era, there are some sectors in the development of coastal areas, because the coastal areas have a very large turnover. At this time the government has been implementing development Surabaya coast. Starting with the construction of the longest bridge in 2004, to date Suramadu bridge provides a very significant impact. Through government Bappeko Surabaya Surabaya developing coastal infrastructure for Surabaya as a public space, with the development of this public space Surabaya government to change the negative image into a positive. Surabaya coastal areas as the initial development of the city of Surabaya as a development step, the coastal area of Surabaya city is divided by some regions of sub-districts and subdistricts Kenjeran Bulak, this region will be developed by the government through Bappeko Surabaya Surabaya. The development of this region is expected to be able to provide a balance to the economy of the coastal area of Surabaya society. This balance is expected to be able to run all the elements that exist in coastal communities Surabaya. At this time the coastal area of Surabaya do not have the image to get an impression of the relevant economics that can be sold to an investor or business owner who can develop the coastal area of Surabaya. It can be seen from the lack of functioning infrastructure such as public facilities and less well-organized travel path elements in the coastal district of Surabaya.